Gender labor income gaps in Costa Rica = Brechas de género en el ingreso laboral en Costa Rica - Saldarriaga, Camilo
Women have lower average labor income than men around the world, despite having more years of education. In developing countries, this situation is often even worse. Women not only face wage gaps compared to men who have the same productivity and the same job, but they also face disadvantages regarding the type and conditions of employment, job stability, unemployment rates, and their caregiving burden. This research analyzes the differences in labor incomes by gender and informality in Costa Rica. To do so, we use the Encuesta Continua de Empleo (ECE) from the first quarter of 2023 to estimate various statistical and econometric methodologies. The analysis is conducted by estimating three econometric methodologies: Mincer's equations, the Oaxaca-Blinder decomposition, and Mincer's equation considering the semi-parametric quantile regression estimation.